The Impact of Social Media-based Marketing Activities on Purchasing Intent Mediated by Social Identity, Perceived Value, and Consumer Satisfaction of Cinere Company - Zeinab Sharifi; Naser Yazdani (مدیریت نوآوری و راهبردهای عملیاتی)
Purpose: The present study aims to investigate the impact of social media marketing activities on the intention to buy Consumers through mediating social identity, perceived value, and consumer satisfaction.Methodology: According to the unlimited community of customers of Cinere Cosmetics Company, 384 people were selected as samples. Data were collected using Chen and Lin's (2019) research questionnaire for analysis, and its validity and reliability were assessed. This research is applied in terms of purpose and descriptive data collection. SPSS and Smart PLS software were used to analyze the collected data.Findings: The results show that social media-based marketing activities positively and significantly affect social identity, perceived value, customer satisfaction, purchase intention, persistence intention, and participation intention. Social identity and perceived value also significantly positively affect customer satisfaction. Customer satisfaction also has a significant positive effect on purchase intention, persistence intention, and participation intention.Originality/Value: The results of this study will be useful for designing a strategic marketing plan for Cinere Cosmetics. They will help managers and marketers find a strategy to increase their brand performance by defining specific factors related to the intention to buy the customer's perceived value. In addition, design the social identity of the brand.